Suicidal ideation among Malaysian youth, prevalence, predictor and prevention: a systematic review - Abdullah Hashim, Haniff; Hassan, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
This systematic review is a type of “research library” to collect, filter, identify and present the result as a comprehensive paper. A total of 12 documents had been analysed. Three themes were extracted from the reviewed documents, (i) Discussion about comparison by demographic to review demographic factor lead to suicidal ideation- relation between gender, race and age with suicidal ideation. (ii) Prevalence and predictor in suicidal ideation or behavior for the prevention and intervention action- depression, anxiety, stress, hopelessness, and self esteem. External factors such as break up steady love, loss something valuable, bully victim, smoking, abuse and substance usage and (iii) Prevention – as a suggestion from the researchers that have been made and reviewed in these papers - relationship with parents, perception about belief system/faith, religious commitment, self efficacy and closeness relationship with parent and encourage of hopefulness.